Statična apneja na vdih in izdih v vodi in na kopnem - Koštomaj, Aleš (Šport (Ljubljana), 2017)
The main purpose of the research involving eight Slovenian men divers on the breath, was to compare the effects of static apnoea after inhalation and after exhalation carried out in water and on land. The divers that were measured have been in the regular training process for many years, and they are considered to be excellent breath-hold divers at national and world levels. Each diver performed static apnoeas in water, two maximum static apnoeas done after breathing in and two after breathing out. And then each diver did the same on land. We measured the following variables: the time duration of each apnoea, the beginning of a spontaneous contraction of the respiratory muscles, the heart rate, systolic blood pressure, diastolic blood pressure and blood saturation with oxygen. According to our results, it can be concluded that with the variable heart rate the training of static apnoea after breathing in on land does not have a similar effect on the body and regulating mechanisms as the training of static apnoea after breathing in in water. The results, on the otherhand, show that it can be assumed that the training of static apnoea after breathing out on land has the effects similar to the ones of the training of static apnoea after breathing out in water. Thus the training of static apnoea after breathing out on land can be suggested as a good supplement for the training of static apnoea after breathing out in water. The results of this study are one of the first important steps in Slovenia when selecting an appropriate training process of breath-hold divers.
Keywords: blood pressure; blood saturation with oxygen; breath-hold diving; diving; frekvenca srca; heart rate; krvni tlak; potapljanje na dih; spiometrija; spirometry; sport; static apnoea; statična apneja; šport; zasičenost krvi s kisikom